The Burden of Autosomal Recessive Congenital Ichthyoses on Patients and their Families: An Italian Multicentre Study - Damiano Abeni; Roberta Rotunno; Andrea Diociaiuti; Simona Giancristoforo; Domenico Bonamonte; Angela Filoni; Carmelo Schepis; Maddalena Siragusa; Iria Neri; Annalucia Virdi; Daniele Castiglia; Giovanna Zambruno; et al. (Medical Journals Sweden, 2021)
Autosomal recessive congenital ichthyoses (ARCI) are characterized by generalized skin scaling, hyperkeratosis, erythroderma, and disabling features affecting the skin (palmoplantar keratoderma, fissures, pain, itch), eyes, ears, and joints. Disease severity and chronicity, patient disfigurement, and time and costs required for care impose a major burden on quality of life. This multicentre cross-sectional study investigated the impact of ARCI on quality of life of patients and families, using the Dermatology Life Quality Index (DLQI), the Children DLQI (CDLQI) and Family Burden of Ichthyosis (FBI) questionnaires. Disease severity was assessed by a dermatologist. A total of 94 patients were recruited, of whom 52 (55.3%) children. Mean age was 20.1 (median 13.5) years. The mean CDLQI/DLQI score was 7.8, and 21 patients scored >10, indicating a major impairment in quality of life: symptoms, feelings and treatment problems were the most affected domains of quality of life. FBI showed a major repercussion on psychological factors and work. The results of this study highlight the impact of ARCI on specific aspects of patient and family life, underlining the need for psychological support.